2018
DOI: 10.1111/tran.12274
|View full text |Cite
|
Sign up to set email alerts
|

Public sector procurement and ethical trade: Governance and social responsibility in some hidden global supply chains

Abstract: This paper places a critical spotlight on the ways in which governance and social responsibility concerning labour standards work in the context of public sector procurement. Supply chains provisioning the public sector, incorporating a vast array of materials used in public services such as education, health, social housing and transportation, have been under‐researched and under‐theorised in the geographical and wider social science literature on Global Production Networks, Global Value Chains and consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…Furthermore, in a significant number of cases analyzed, the state's buyer role was aimed at achieving improved environmental performance at a local level (Table 2). Such evidence is in line with the increased emphasis on (social and environmental) responsibility that governments, especially in developed countries, are placing on their purchasing activities (see Hughes et al, 2019).…”
Section: State As Buyersupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, in a significant number of cases analyzed, the state's buyer role was aimed at achieving improved environmental performance at a local level (Table 2). Such evidence is in line with the increased emphasis on (social and environmental) responsibility that governments, especially in developed countries, are placing on their purchasing activities (see Hughes et al, 2019).…”
Section: State As Buyersupporting
confidence: 66%
“…Our review also found that few studies examined the state's role as buyer in relation to GVC-oriented policies, perhaps due to the fact that public sector procurement is a new and emerging focus of GVCs/ GPNs research (Hughes et al, 2019). The few examples observed were primarily in the context of complex product GVCs located in upper-middle or high-income economies (Table 3).…”
Section: State As Buyermentioning
confidence: 93%
“…The role of the state as a producer through state-owned companies, although a greater emphasis in international business research (e.g., Cuervo-Cazurra, Inkpen, Musacchio, & Ramaswamy, 2014 ), has still to receive considerable attention in relation to GVCs. Nevertheless, emerging research has focused on the state buyer role in terms of public procurement (Hughes, Morrison, & Ruwanpura, 2019 ). More broadly, growing attention has been placed on the active ways states are shaping their engagement with global trade (Evenett, 2019 ), including through industrial policy (Hauge, 2020 ; Kaplinsky & Morris, 2015 ; Whitfield, Staritz, & Morris, 2020 ).…”
Section: Gvcs States and Development: Beyond Export-oriented Develomentioning
confidence: 99%
“…Procurement remains a crucial if underappreciated modality of state action that shapes global production networks in largely unexplored ways. Hughes, Morrison and Ruwanpura (2019) study the introduction of ethical codes for supply chains into government procurement policies in a variety of sectors in the UK, efforts that are hampered by the legal context and absence of consumer pressure (see also Martin-Ortega, 2018). The state-as-buyer role is more often used to shore up domestic producers, for example, in food procurement for hospitals, schools, and food aid programs.…”
Section: The State-global Production Network Nexus: Expanding Statmentioning
confidence: 99%